Determinants of excellent/good self-rated health among HIV positive individuals in South Africa: evidence from a 2012 nationally representative household survey - M. L. H. Mabaso; N. P. Zungu; T. Rehle; S. Moyo; S. Jooste; K. Zuma (BMC, 2018)
Abstract Background In South Africa, HIV is increasingly becoming a chronic disease as a result of advances in HIV treatment and prevention in the last three decades. This has changed the perception from a life threating to a potentially manageable disease. However, little is known about self-perceived health status of HIV-infected individuals. Self-rated health (SRH) has been shown to be a sensitive indicator of health-relatedchanges directly linked to HIV, but can also be influenced by differences in social and material conditions. The aim of this paper was to identify determinants of excellent/good SRH among HIV-infected individuals using socio-demographic, life style and health related data. Methods The study used data from the nationally representative 2012 South African population-based household survey on HIV prevalence, incidence and behaviour conducted using multi-stage stratified cluster sampling design. Bivariate and multivariate logistic regression models were used to identify determinants of SRH among HIV-infected individuals. Results Out of a total of 2632 HIV positive participants 74.1% (95% CI: 68.4-74.2) reported excellent/good SRH. Increased likelihood of reporting excellent/good SRH was significantly associated with being Black African [OR= 1.97 (95%CI: 1.12-3.46), p = 0.019] and belonging to least poor household [OR= 3.13 (95%CI: 1.26-7.78), p = 0.014]. Decreased likelihood of reporting excellent/good SRH was significantly associated with those aged 25 to 34 years [OR= 0.49 (95% CI: 0.31-0.78), p = 0.003], 35 to 44 years[OR= 0.27 (95% CI: 0.17-0.44), p < 0.001], 45 to 54 years [OR= 0.20 (95% CI: 0.12-0.34), p < 0.001], and those 55 years and older [OR= 0.15 (95% CI: 0.09-0.26), p < 0.001], hospitalization in the past twelve months [OR= 0.40 (95% CI: 0.26-0.60), p < 0.001]. Conclusion To have positive health effects and improve the perceived health status for PLWH social interventions should seek to enhance to support for the elderly HIV-positive individuals, and address the challenge of socio-economic inequalities and underlying comorbid conditions resulting in hospitalization.